Ruptured secondary abdominal pregnancy after primary laparoscopic treatment for tubal pregnancy: A case report. Issue 50 (December 2017) - Zhang, Duoduo; Chen, Anxia; Gu, Yu
Abstract: Introduction: Most secondary abdominal pregnancies happen after spontaneous abortion of tubal pregnancy or ruptured intrauterine pregnancy. However, we presented a case of ruptured secondary abdominal pregnancy after primary laparoscopic treatment of tubal pregnancy. Case report: The ectopic pregnant lesion in the affected tube was thoroughly removed in the primary laparoscopy, and nothing abnormal was detected in abdomen or pelvis. Beta human chorionic gonadotropin levels dropped significantly after surgery, but the patient came back again for severe abdominal pain with beta human chorionic gonadotropin increasing, and free peritoneal fluid in the pouch of Douglas was detected at ultrasonography. The secondary laparoscopy was done according to the intraperitoneal hemorrhage and unstable vital signs. The secondary pregnancy was found ruptured in the splenic flexure of the colon. Although several cases of secondary abdominal pregnancies were reported in the literature, herein we describe a case secondary to the salpingotomy of the primary tubal pregnancy. Conclusion: After surgery for ectopic pregnancy, the patient's serum beta human chorionic gonadotropin levels should be closely followed until negative. When persistent ectopic pregnancy was suspected after surgery, physicians should keep in mind a rare possibility of secondary abdominal pregnancy.